2021
DOI: 10.1002/cbdv.202001069
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Mechanism of Costunolide‐Induced MCF‐7 Cells Apoptosis by Multi‐Spectroscopy, Molecular Docking and Cell Experiments

Abstract: Breast cancer is one of the most common cancer with high morbidity and mortality in women. This study aimed to explore the potential mechanism of costunolide inducing MCF‐7 cells apoptosis by multi‐spectroscopy, molecular docking, and cell experiments. The results manifested that costunolide interacted with calf thymus DNA (ct‐DNA) in a spontaneous manner, and the minor groove as the preferential binding mode. Furthermore, costunolide inhibited cell proliferation and colony formation. Hoechst 33258 staining sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Studies have found that DNA damage will lead to the activation of mitochondria‐dependent apoptotic pathway that is mediated by Bcl‐2 protein family [76] . The Bcl‐2 family is a classic pathway that regulates intrinsic apoptosis, and it comprises several pro‐apoptotic (such as Bax) and anti‐apoptotic proteins (such as Bcl‐2) [35,77] . In previous studies, the results indicated that MGO induced DNA damage in HEK293 cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have found that DNA damage will lead to the activation of mitochondria‐dependent apoptotic pathway that is mediated by Bcl‐2 protein family [76] . The Bcl‐2 family is a classic pathway that regulates intrinsic apoptosis, and it comprises several pro‐apoptotic (such as Bax) and anti‐apoptotic proteins (such as Bcl‐2) [35,77] . In previous studies, the results indicated that MGO induced DNA damage in HEK293 cells.…”
Section: Resultsmentioning
confidence: 98%
“…HEK293 cells were seeded into 96‐well plates at a density of 6×10 3 cells/well. The cells were exposed to different concentration of MGO (0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75 and 2 mM) for 24 h. Subsequently, the cells were incubated with 20 μl MTT (5 mg/mL) in the dark at 37 °C for 4 h. 150 μl dimethyl sulfoxide (DMSO) was added to each well [77] . Finally, the absorbance was measured at 490 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Combination treatment of costunolide and dehydrocostuslactone could inhibit breast cancer by inducing cell cycle arrest and apoptosis[ 94 ]. The control of Bax, Bcl-2, p53, Caspase-3 protein production as well as the activation of the p38MAPK and nuclear factor-B (NF-B) pathways were essential components of the apoptotic mechanism[ 95 ].…”
Section: Development Usps Inhibitors In Breast Cancer Treatmentmentioning
confidence: 99%